Evaluasi APAR Berdasarkan Permenakertrans Nomor 4 Tahun 1980 di PT.XY - Alfina Novita Dewi; Muslikha Nourma Rhomadhoni; Ratna Ayu Ratriwardhani; Bondan Winarno (Peneliti.net, 2022)
Losses caused by fires that occur in industry are very large, because they involve high asset values, and can cost lives. Fires can occur anywhere, one of which is in the office building of PT. XY which is classified as a light fire hazard. One form of security and prevention against fires is the installation of fire extinguishers. The purpose of this study was to evaluate the suitability of the application of a light fire extinguisher. The type of research in this study is qualitative, namely by comparing the actual condition of light fire extinguishers in the field with the Minister of Manpower and Transmigration Regulation Number 04 of 1980 through observation, interviews, documentation and measurement of the height and distance of the fire extinguisher. The results showed that the number of fire extinguishers as a whole was not appropriate, the type of fire extinguisher had been fulfilled properly, the condition of the fire extinguisher was still not up to standard, the placement of the fire extinguisher was still quite good at the distance between fire extinguishers but there were still some that were not suitable, the maintenance of the fire extinguisher was well maintained but still needs control and the level of knowledge of workers regarding the use of fire extinguishers is quite good but needs to be improved again because there are still some employees who have not received fire training. The conclusion that PT.XY, the, has implemented fire prevention by installing fire extinguisher, there are several indicator components that are not appropriate. Suggestions that can be given are to improve the fire extinguisher indicators that are not appropriate and always carry out routine monitoring to improve fire extinguisher maintenance and provide fire training to workers.